Experimental and simulation study on the impact of storage and recovery of coastal aquifer to seawater intrusion - Wang, Zhiwei; Chen, Huawei; Li, Fulin; Wang, Genxu (Natural hazards (Dordrecht), 2022)
It is of great significance for the reasonable development and utilization of coastal aquifers and alleviation of water stress to study the migration law of seawater intrusion and the storage and recovery of underground aquifers in coastal areas. Under the premise of a certain amount of single well recharge, the physical model of the indoor sand box is constructed to study the migration law of the fresh-saline groundwater interface and the storage and recovery of the coastal aquifer under the superimposed well layout method, and analyze the recovery rate in different experimental schemes under the premise of preventing the increase of seawater intrusion. Finally, for comparing and analyzing the results of the experiment and simulation and carrying out related research, after further increasing the recharge volume of aquifer, FEFLOW software was used. The results show as follows: Under the premise of a certain amount of single well recharge, with the increase of the number of wells in the plan, the retreat area of the saline wedge increases from 20 to 1600 cm 2 , and the recovery rate of aquifer increases from 18.89 to 42.50%. At the same time, the simulation of FEFLOW software is basically consistent with the experimental results of the indoor sand box. Under the premise of certain well layout method, after increasing the single well recharge volume, the retreat area of the saline wedge is increased from 1600 to 2050 cm 2 , and the recovery rate of the aquifer increased from 42.50 to 48.96%. Therefore, the storage and recovery of water resources in coastal aquifers can be achieved through the arrangement of recharge and recovery wells. Under the premise of preventing the increase in seawater intrusion, the water resources stored in the aquifer can be increased by increasing the number of wells and the amount of recharge water. This study provides a basis for the rational development and sustainable use of coastal aquifers.